Pengaruh Perbandingan Massa Silikon/Silika terhadap Karbon pada Kinerja Anode Baterai Litium Ion dari Sekam Padi - Achmad Rochliadi; Mohammad Alief Ramdhan; Aep Patah (Universitas Andalas, 2023)
This study aims to investigate the possible utilization of silica (SiO2) and silicon (Si) derived from rice husks as anode materials in lithium-ion batteries (LIBs). SiO2 and Si have impressive theoretical capacities of 1965 and 4200 mAh/g, respectively. However, their direct use as LIBs anodes faces challenges such as substantial volume changes during battery charging and discharging, as well as low electrical conductivity. Consequently, a common approach is to create nanostructures of SiO2 and Si, such as nanoparticles, nanowires, and nanotubes, and combine them with conductive matrices like carbon-based materials. In this study, the Si/SiO2/C composite was synthesized from rice husks, taking into account the mass ratio of Si/SiO2 to C. The process involved first separating SiO2 and C from rice husks and then synthesizing the composite using the ball mill method and activated molten salt aluminothermic reduction (AlCl3/NaCl). X-ray Diffraction (XRD) analysis confirmed the successful synthesis of the composite, as indicated by characteristic peaks of the constituent compounds. Scanning Electron Microscope (SEM) imaging showed non-uniform morphology with varying particle sizes. Tests results demonstrated that the Si/SiO2/C composite with a 3:1 ratio exhibited the most promising performance as a LIB anode, maintaining a high capacity of 280.48 mAh/g with a Coulombic Efficiency (CE) of 99% after 50 testing cycles. These findings suggest that silica and silicon compounds derived from rice husks hold great potential as efficient and durable anode materials for LIBs applications.